Hrvatske autohtone manjine u Europskoj uniji - Dekić, Marko (Array, 2006)
An interview with Mijo Karagić, president of the Croatian National Self-Government in Hungary, who has stood at the helm of this respectable organisation since the very beginnings (1995) of a minority system in Hungary. He has acquired a wealth of experience, created a wide network of contacts with numerous politicians, diplomats, experts and journalists across Europe. Mr. Karagić has established close cooperation with the Croatian communities in Austria, Italy, Macedonia, Romania, the Czech Republic, Slovakia, Serbia and Montenegro and is therefore an excellent collocutor on the subject of Croatian minorities in the EU. He is a member of the Croatian Writers' Society (DHK) and was, from 1997 to 2003 the president of the indigenous Croatian communities in neighbouring countries. He was in 1999 appointed an honorary Croatian Consul to Hungary. That country has been, as of 2004, a member of the European Union. Croatians from various European countries will, finally, live in an atmosphere and environment in which the Croatian identity cannot be discriminated against or castigated says Mijo Karagić. He believes that the Croatian community living outside Croatia will jointly seek appropriate answers to new social and political challenges